KONDISI EFEKTIF PESERTA DIDIK DALAM PROSES PEMBELAJARAN DI SMK MUHAMMADIYAH 4 SURAKARTA - Rohmatillah, Abidah; Septiani, Aldila; Maysaroh, Efi; Roziaty, Efri; Purnamasari, Indah; Alfianti, Meilinia Nurul (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The writing of this scientific article aims to know the effective condition of learners in the learning process at SMK Muhammadiyah 4 Surakarta. These effective conditions are important things that we should be mindful of. Because it is in this condition that students are able to receive science delivered by teachers easily. To achieve this situation, a teacher should take into account what factors affect the learning process, what a student needs during the learning process. So with this research we observe to know what is the effective condition of learners in the learning process. We use qualitative method with direct observation and student interviews in the X-Class of pharmacy at SMK Muhammadiyah 4 Surakarta. The results of this study were obtained that most students and teachers have both applied effective learning conditions.